The effect of perineural injection therapy on neuropathic pain: a retrospective study - Kim, Haekyu; Kim, Hyae Jin; Jung, Young-Hoon; Do, Wangseok; Kim, Eun-Jung (Journal of dental anesthesia and pain medicine: JDAPM, 2024)
Among the various pain-related diseases that can be encountered at the clinic, there is a neuropathic pain that is difficult to treat. Numerous methods have been proposed to treat neuropathic pain, such as taking medication, nerve block with lidocaine, or neurolysis with alcohol or phenol. Recently, a method of perineural injection using dextrose instead of lidocaine was proposed. This study was designed to compare the effects of perineural injection therapy (PIT) with buffered 5% dextrose or 0.5% lidocaine on neuropathic pain. The data were collected from the database of pain clinic from August 1st, 2019 to December 31st, 2022 without any personal information. The inclusion criteria were patients diagnosed with postherpetic neuralgia (PHN), trigeminal neuralgia (TN), complex regional pain syndrome (CRPS), or peripheral neuropathy (PN), and patients who had undergone PIT with buffered 5% dextrose (Dextrose group) or 0.5% lidocaine (Lidocaine group) for pain control. The data of patients, namely sex, age, and pain score (numerical rating scale, NRS) were collected before PIT. The data of NRS, side effects, and satisfaction grade (excellent, good, fair, or poor) were collected one week after each of the four PIT, and two weeks after the last PIT. Overall, 112 subjects were enrolled. The Dextrose group included 89 and Lidocaine group included 23 patients. Because the number of patients in the Lidocaine group was too small to allow statistical analysis, the trend in Lidocaine group was just observed in each disease. There were no significant side effects except for a few bruise cases on the site of injection in all groups. The NRS in most Dextrose groups except CRPS were reduced significantly; however, the Lidocaine group showed a trend of pain reduction only in PHN. The Dextrose group except CRPS showed increased satisfaction two weeks after the final PIT. From the results, it is suggested that PIT with buffered 5% dextrose may have a good effect for neuropathic pain without any side effect except for patients with CRPS. This may offer a window into a new tool that practitioners can employ in their quest to help patients with neuropathic pain.